The effects of women's double working hours on professional nursing practice (Research, Society and Development, 2024)
Objective: Reflect on the double working day of female nurses and its consequences for professional practice. Methodology: This is a theoretical and reflective study based on the theoretical perspective of the sociology of work, together with the theoretical references of Simone de Beauvoir and Karl Marx and Friedrich Engels. A narrative review of the literature was carried out in a non-systematic way in order to establish relationships between the theoretical framework selected and current issues in nursing, as well as women's experiences. Results: The logical-reflective exposition is anchored in three fundamental aspects: the working nurse; the double working day and the health of working nurses. It's not possible to look at women only as workers, since their biological reality is closely linked to their social representation.  This implies the need to investigate how the social construction of women directly interferes with their lives in an integral way. Such reflection can contribute to valuing nursing work, as well as fostering discussion about the social role of women. Conclusion: This reflection needs to be present in society as a whole, not just in the context of nursing, so that women's demands, which have been evident throughout history, can be noted.